Research on the NB-IoT Random Access in LEO Satellite IoT - Haodong LIU; Zhong ZHENG; Wenjin WANG; Li YOU; Xiqi GAO (天地一体化信息网络)
Narrowband internet of things (NB-IoT) technology is widely used in data communications for a large number of low-speed and low-power devices, but it is diff cult to provide services for remote areas that cannot be covered by terrestrial networks.With its global coverage and low cost, the LEO satellite constellation can supplement and expand the terrestrial NB-IoT infrastructure, providing an eff ective solution for the space-based internet of things.Facing the application requirements of space-based internet of things, on the basis of reviewing the NB-IoT system architecture, the challenges of channel environment high dynamic delay and frequency off set faced by the application of NB-IoT technology in the LEO satellite constellation scenario were analyzed.For the uplink random access process, an eff ective user detection and timing synchronization method was designed, which had the advantages of high performance and low complexity, and provided an eff cient receiving method for the LEO satellite NB-IoT uplink random access synchronization.